Magnetic Resonance Cholangiopancreatography with Secretin Stimulation in the Diagnosis of Intraductal Papillary Mucinous Neoplasm: A Paradigmatic Case Report - Elsa Iannicelli; Francesco Carbonetti; Marco Di Pietropaolo; Giulia Francesca Federici; Gabriele Capurso; Vincenzo David (Case Reports in Radiology)
Context. One of the characteristic findings of intraductal papillary mucinous neoplasms (IPMN) is the presence of a direct communication between the lesion and the ductal pancreatic system and when magnetic resonance cholangiopancreatography (MRCP) shows uncertain findings, it is useful to perform a MRCP after secretin stimulation (MRCP-S) which provides a better visualization of the ductal system. Case Report. We present a case of 51-year-old man in whom, during a CT follow-up for a renal tumour, was found a cystic lesion of the pancreas. To better evaluate the lesion and its suspected communication with the pancreatic system, MR with gadolinium and MRCP and MRCP-S were performed. With the MRCP and MRI it was not possible to identify a clear communication between the cystic lesion and the ductal system. MRCP-S showed an increase in signal intensity of the lesion and its communication with the ductal system, allowing us to classify the cystic lesion as a main duct in intraductal papillary mucinous neoplasm. The patient underwent a surgical duodenal pancreatectomy. The histological result of the specimen confirmed the diagnosis of adenocarcinoma IPMN. Conclusion. In this case MRCP-S has allowed a clearer identification of the cystic lesion allowing a correct diagnosis and treatment.